Seascape genetics in a polychaete worm: Disentangling the roles of a biogeographic barrier and environmental factors. (12th October 2022) - Mendes, Cecili B.; Cortez, Thainá; Santos, Cinthya S. G.; Sobral‐Souza, Thadeu; Santos, Arian Dielactaquiz; Sasaki, Dalton Kei; Silva, Danilo Augusto; Dottori, Marcelo; Andrade, Sónia C. S.
Abstract: Aim: Seascape genomic studies aim to understand how environmental variables shape species diversity through genotype–environment associations. Identifying these effects on lecithotrophic larval species that live in intertidal zones is particularly challenging because they are subject to environmental heterogeneity and anthropogenic events. Here, we evaluate how biotic and abiotic features in the Southwest Atlantic littoral zone can affect a high dispersal species' present and historical demography. Location: Brazilian coast, covering more than 3000 km. Taxon: Perinereis ponteni. Methods: We investigated population genetic diversity, connectivity and past dynamics using 23, 300 single‐nucleotide polymorphisms (SNPs) generated using genotyping by sequencing. We tested whether environmental abiotic variables could explain the variance found in genotype frequencies using isolation‐by‐environment (IBE) and landscape association approaches. These data, combined with palaeodistribution simulations and oceanic circulation modelling, were used to infer species demographic history and connectivity patterns. Results: Along with high levels of connectivity detected, we found a genetic boundary in the southeastern region of Brazil around Cabo Frio (Rio de Janeiro), and a cline trend for some loci. The palaeodistribution simulations reveal a spatial refuge in the southeast during the Last Glacial Maximum (21 kya), with the expansion of the northern region. We identified 1421 SNPs with frequencies associated with eight environmental variables, most of which were related to temperature—the main environmental factor determining IBE. Main Conclusions: Perinereis ponteni, a polychaete with high gene flow capability responds to biogeographic barriers, highlighting the importance of biotic and abiotic factors in shaping population connectivity. Furthermore, the effect of temperature indicates that future climate change and ocean warming can hugely impact this species.